2002
DOI: 10.1016/s0969-2126(02)00747-5
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Mechanism of the Type II Dehydroquinase from Streptomyces coelicolor

Abstract: The structure of the type II DHQase from Streptomyces coelicolor has been solved and refined to high resolution in complexes with a number of ligands, including dehydroshikimate and a rationally designed transition state analogue, 2,3-anhydro-quinic acid. These structures define the active site of the enzyme and the role of key amino acid residues and provide snap shots of the catalytic cycle. The resolution of the flexible lid domain (residues 21-31) shows that the invariant residues Arg23 and Tyr28 close ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
128
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 41 publications
3
128
1
Order By: Relevance
“…In the absence of any crystal structure and based on kinetic isotope effects and pH profile studies carried out on Mt-DHQ2 and Aspergillus nidulans DHQ2 (An-DHQ2), Harris et al [41] suggested that the elimination proceeds by a stepwise E 1 CB mechanism via enolate intermediate 26 (Scheme 2). Subsequent resolution of the DHQ2 from Streptomyces coelicolor (Sc-DHQ2) with an inhibitor in the active site (PDB entry 1GU1, 1.8 Å) by Roszak et al [42] allowed a detailed description of the active site and provided a good knowledge of the specific functions of individual amino acid residues. The substrate is strongly bound to the active site by a series of hydrogen bonding interactions through the carboxylate group and the three hydroxyl groups.…”
Section: Mechanism and Substrate Bindingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the absence of any crystal structure and based on kinetic isotope effects and pH profile studies carried out on Mt-DHQ2 and Aspergillus nidulans DHQ2 (An-DHQ2), Harris et al [41] suggested that the elimination proceeds by a stepwise E 1 CB mechanism via enolate intermediate 26 (Scheme 2). Subsequent resolution of the DHQ2 from Streptomyces coelicolor (Sc-DHQ2) with an inhibitor in the active site (PDB entry 1GU1, 1.8 Å) by Roszak et al [42] allowed a detailed description of the active site and provided a good knowledge of the specific functions of individual amino acid residues. The substrate is strongly bound to the active site by a series of hydrogen bonding interactions through the carboxylate group and the three hydroxyl groups.…”
Section: Mechanism and Substrate Bindingmentioning
confidence: 99%
“…WAT1 interacts through hydrogen bonding with a conserved asparagine (Asn10/Asn12 in Hp-DHQ2 and Mt-DHQ2, respectively), the carbonyl group of a conserved proline (Pro9/Pro11 in Hp-DHQ2 and Mt-DHQ2, respectively) and the main-chain amide of a glycine or an alanine (Ala79/Gly78 in Hp-DHQ2 and Mt-DHQ2, respectively). Initially, it was proposed that WAT1 would be involved in the enzymatic mechanism [42]. However, QM/MM studies suggest that WAT1 would be mainly involved in the stabilization of the substrate and enol intermediate 32 [44].…”
Section: Mechanism and Substrate Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] In contrast, the type II dehydroquinases are dodecamers that facilitate the anti-elimination of water via an E 1CB mechanism, whereby abstraction of the more acidic pro-S hydrogen (H S , Scheme 1) is facilitated by a conserved tyrosine residue, resulting in the formation of an enol intermediate 3 (Scheme 1). [7,11,12] Type II dehydroquinases are present in pathogenic bacteria such as Mycobacterium tuberculosis, [13] the etiological agent of tuberculosis (TB), and Helicobacter pylori, [14] a stomach pathogen that causes gastric ulcers and is linked to the development of stomach cancer. Due to the increased resistance of these and other microorganisms to current chemotherapies, antibacterial agents with novel mechanisms of action are required.…”
mentioning
confidence: 99%